«Quechua» y el sistema inca de denominación de las lenguas - César Itier (Mélanges de la Casa de Velázquez, 2015)
In speaking of the «tongue called Quichua» or simply the «Quichua tongue» the Spanish adopted the Incaic endonym qhichwa simi or «language of the valleys». This expression designated the Quechua koiné which took form and was propagated in the temperate valleys of the Andes where the Incas had introduced large numbers of settlers from diverse linguistic backgrounds. Qhichwa simi stood in opposition to hawa simi or the «tongue from above/from outside» which designated the local languages used by the population inhabiting higher ground since an earlier period. This semantic opposition reveals the central role of the Quechua «of the valleys» in the Incaic system of communication.